3 English Houses, Materiality, and Everyday Life. Issue 1 (September 2015) - Johnson, Matthew H.; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT My previous work developed a structural model for understanding English vernacular houses, stressing the way the house reflected wider household values. In this paper, I balance this account by starting with everyday life rather than formal structure. I examine material traces of dwelling within and around the house, rather than the presumed mental template that conditioned its building. I discuss material items that flowed through the house in sometimes unpredictable and alarming ways (for example through witchcraft). These artifacts reflect gendered tensions and anxieties that ran through the rhythms of everyday life, rather than a patriarchal structure that governed them. A focus on dwelling brings into focus how the material form of the house and the social form of the household mutually created each other.